Mouse Adapted SARS‐CoV‐2 induces 'long‐COVID' neuropathology in BALB/c mice. (20th December 2022) - Gressett, Timothy E; Ismael, Saifudeen; Narayanappa, Amruta; Biose, Ifechukwude Joachim; Leist, Sarah R; Baric, Ralph S; Bix, Gregory J
Abstract: Background: COVID‐19 survivors develop neuro‐psychological symptoms as post‐COVID 19 syndromes, although the pathophysiology remains elusive. SARS‐CoV‐2 MA10 (MA10) is a model of mouse‐adapted SARS‐CoV‐2 that recapitulates acute respiratory distress syndrome observed in humans. However, the consequence of MA10 infection on brain pathology is not yet evaluated. The study aimed to evaluate the long‐term consequence of MA10 infection on blood‐brain barrier (BBB) integrity and neuroinflammation Method: 10‐week and 12‐months old female BALB/c/cAnNHsd mice were infected intranasally with 10 4 PFU and 10 3 PFU SARS‐CoV‐2 MA 10 respectively. The brain was isolated 60‐ and 120‐days post‐infection (60 and 120 dpi) and subjected to histological analysis and mRNA expression by qPCR array. Result: Immunohistochemical analysis showed that MA 10 infection caused increased GFAP immunoreactivity in young mice. Histopathological analysis showed that MA10 infection induced significant neuropathology. Ongoing quantification on microglial activation and BBB integrity elucidated a possible correlation between infection and neuropathology. Conclusion: Our data shows the first time that MA10 infection induces neuropathological outcomes several weeks after infection. These observations can help to develop novel therapeutic strategies to ameliorate neuroinflammation and restore brain function